2020
DOI: 10.5114/aoms.2020.100366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics, treatment, in-hospital and 12-month outcomes in patients after myocardial infarction with ejection fraction < 40% with or without atrial fibrillation

Abstract: IntroductionThe study aimed to compare the characteristics, treatment, and 12-month outcomes of patients after myocardial infarction (MI) and with left ventricular ejection fraction (LVEF) < 40%, with or without atrial fibrillation (AF).Material and methodsThe analysis involved 10,222 surviving patients who were enrolled in the ongoing, prospective Polish Registry of Acute Coronary Syndromes (PL-ACS). The major adverse cardiac events (MACE) involved death, non-fatal MI, rehospitalization due to heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it may be concluded that the increase of data sets and the use of more complex variables, such as digital electrocardiograms or diagnostic images, may reveal the superiority of NN over the LR approach [14]. One of the primary purposes of analyses performed in the PL-ACS registry is to identify the clinically significant predictors of unfavorable events and patients with high mortality risk [21][22][23]. The post-STEMI risk stratification is an important clinical issue highlighted in the "Gaps in the evidence and areas for future research" section of the European Society of Cardiology guidelines for the management of acute myocardial infarction in patients presenting with ST-segment elevation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be concluded that the increase of data sets and the use of more complex variables, such as digital electrocardiograms or diagnostic images, may reveal the superiority of NN over the LR approach [14]. One of the primary purposes of analyses performed in the PL-ACS registry is to identify the clinically significant predictors of unfavorable events and patients with high mortality risk [21][22][23]. The post-STEMI risk stratification is an important clinical issue highlighted in the "Gaps in the evidence and areas for future research" section of the European Society of Cardiology guidelines for the management of acute myocardial infarction in patients presenting with ST-segment elevation [24].…”
Section: Discussionmentioning
confidence: 99%